Structural brain injury in patients with disorders of consciousness: A voxel-based morphometry study. (23rd February 2016) - Guldenmund, Pieter; Soddu, Andrea; Baquero, Katherine; Vanhaudenhuyse, Audrey; Bruno, Marie-Aurélie; Gosseries, Olivia; Laureys, Steven; Gómez, Francisco
Abstract: Main objective : Disorders of consciousness (DOC; encompassing coma, vegetative state/unresponsive wakefulness syndrome (VS/UWS) and minimally conscious state minus/plus (MCS–/+)) are associated with structural brain injury. The extent of this damage remains poorly understood and merits a detailed examination using novel analysis techniques. Research design/methods and procedures : This study used voxel-based morphometry (VBM) on structural magnetic resonance imaging scans of 61 patients with DOC to examine grey and white matter injury associated with DOC, time spent in DOC, aetiology and diagnosis. Main outcomes and results : DOC and time spent in DOC were found to be associated with widespread structural brain injury, although the latter did not correlate strongly with injury in the right cerebral hemisphere. Traumatic, as compared to non-traumatic aetiology, was related to more injury in the brainstem, midbrain, thalamus, hypothalamus, basal forebrain, cerebellum, and posterior corpus callosum. Potential structural differences were found between VS/UWS and MCS and between MCS– and MCS+, but need further examination. Conclusions : The findings indicate that both traumatic and non-traumatic DOC are associated with widespread structural brain injury, although differences exist that could lead to aetiology-specific treatment strategies. Furthermore, the high degree of atrophy occurring after initial brain injury prompts the development and use of neuroprotective techniques to potentially increase patients' chances of recovery.